2019
DOI: 10.1002/dc.24214
|View full text |Cite
|
Sign up to set email alerts
|

The risk of malignancy according to Milan reporting system of salivary gland fine‐needle aspiration with Becton Dickinson SurePath liquid‐based processing

Abstract: Background Fine‐needle aspiration cytology (FNAC) is a noninvasive, safe, cost‐effective, diagnostic procedure for the evaluation of salivary gland lesions and the selection of patients for surgery. The aim of this study was to analyze the risk of malignancy (ROM) according to the Milan reporting system of salivary gland FNA specimens using a liquid‐based cytology (LBC) technique. Methods The cytological diagnosis of 459 cases between 2014 and 2017 was revised according to the Milan reporting system. The FNAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 21 publications
(57 reference statements)
0
22
1
Order By: Relevance
“…Among all FNAs with histological follow-up, 22 out of 90 cases (24.4%) were non-neoplastic lesions, whereas 68 lesions (75.6%) were neoplastic and 16 lesions (17.8%) were malignant. The risk of neoplasm, the risk of malignancy, and the overall risk of malignancy were calculated for each MSRSGC category (Table 3) and compared with other MSRSGC studies [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26] and MSRSGC estimated ROMs (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Among all FNAs with histological follow-up, 22 out of 90 cases (24.4%) were non-neoplastic lesions, whereas 68 lesions (75.6%) were neoplastic and 16 lesions (17.8%) were malignant. The risk of neoplasm, the risk of malignancy, and the overall risk of malignancy were calculated for each MSRSGC category (Table 3) and compared with other MSRSGC studies [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26] and MSRSGC estimated ROMs (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 58% of studies exceeded this suggested figure (14.5%‐40.4% of all cases in the ND category). The use of US‐guided FNA decreases the percentage ND cases, 38 and some studies showed that conventional smears have lower ND rates compared to liquid‐based preparations 35 …”
Section: Discussionmentioning
confidence: 99%
“…Only the studies which separated the NN from the benign neoplastic diagnoses upon histopathological follow‐up were included in calculating the FNA accuracy in detecting neoplasm 11,12,15,17,19,20,22,23,25,26,28,30‐38,40,45 . The studies which solely reported the cytologic‐histopathological correlation among the AUS, SUMP, and/or SM were excluded from the accuracy analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of 6249 reviewed cases performed by the College of American Pathologists, the lymphoma cases featured the highest false-negative rate at 57% [33]. In recent MSRSGC analyses, 10 lymphoma cases were misinterpreted in a non-neoplastic category and 9 lymphoma cases in an AUS category [4,23,25,26,34].…”
Section: Discussionmentioning
confidence: 99%